Investigation of the DMR6 susceptibility genes in grapevine for improving phytoplasma resistance through CRISPR/Cas9 technology - Holm, Clara Cornelia (Stellenbosch : Stellenbosch University, 2024)
Thesis (MScAgric)--Stellenbosch University, 2024.